ANALISIS PELUANG USAHA DAN PENYERAPAN TENAGA KERJA LOKAL TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT DI ISTANA TAMAN CADAS - Nur Komariyah; Wulan Permata Sari; Niken Arieftianty; Ade Fauji (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2026)
This study analyzes the business opportunities and local labor absorption in increasing community income around the Istana Taman Cadas tourist attraction. The background of this research is the limited economic activities of the community before the existence of the tourist site. The development of Istana Taman Cadas has created new jobs, business opportunities, and increased community income. The method used in this research is a qualitative descriptive approach through observation, interviews, and documentation. The results show that the existence of Istana Taman Cadas has absorbed around 20 local workers, opened up small business opportunities such as food and beverage stalls, and significantly increased people’s income, especially during holidays and weekends. The conclusion of this study indicates that the tourism sector contributes positively to the economic empowerment of the surrounding community.